Pelatihan Produksi Videografi Sebagai Bekal Keterampilan Bagi Tahanan Pendamping Rumah Tahanan (Rutan) Kelas 1 Depok - Roni Jayawinangun; Dipo Krishyudi Ono; Yennie Krishnawati Milono (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Correctional assisted persons (Warga Binaan Pemasyarakatan/WBP) are one of the most marginalized communities due to their past unlawful acts. Assisted citizens who have served a period of detention and behaved well will be appointed as companion prisoner (tahanan pendamping /tamping). Therefore, especially for these companion prisoners, skills are needed that can be a provision in living a new life in society. The purpose of this activity is to provide knowledge and skills in the form of video production for tamping in the post-incarceration period. The method used is lectures, practices and assistance in making videos using cellphone cameras to 8 tamping people at the Class I Detention Center in Depok. The results obtained from this activity include an increase in video making skills starting from planning, taking pictures and also video editing. This video can be used either as self-promotion or marketing products through social media. The conclusions of this activity include that accompanying prisoners who have participated in this activity feel the benefits as their provision in the future, 3 out of 8 tamping who have been free have begun to actively make videos in an effort to get alternative income through social media. For accompanying prisoners who are not yet free, they plan to make videos as a means of self-promotion and also market the products they will sell later